Melatonin in physiological/biological ovarian aging - Reiter, Russel (2023)
Melatonin, a highly functionally diverse, low-molecular-weight antioxidant and anti-inflammatoryagent has been sparingly studied relative to its ability to reduce patho-physiological processescommon to the peripheral female reproductive system. Currently it is known that melatoninreduction is associated with multiple processes underlying changes in the ovary, especially late inthe cessation of the reproductive life span. In this sense, it is essential deepen the knowledgeabout the physiological and molecular actions of melatonin in the maintenance of normal ovariesand in the aging ovaries, and integrate the acquired information for considering melatonin in thetreatment of age-related infertility. Additional research is needed to fully understand the effects ofmelatonin supplementation on potentially enhancing fertility, however, studies published to datesuggest it may be a promising option for those struggling with infertility.